Langkah Strategis Guru Fikih dalam Menumbuhkan Iklim Belajar yang Kondusif di MIN 1 Sinjai - Nurhayati, R; Syamsir, Syamsir; Suwito, Agus; Nur, Makmur Jaya (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Teachers as the spearhead of the educational process, play a strategic role in creating and maintaining a conducive learning climate. This study aims to describe the strategies of Fiqh teachers in creating a conducive classroom climate at MIN 1 Sinjai and the obstacles faced in its implementation. The study used a qualitative approach with descriptive methods, and data collection techniques through interviews, observation, and documentation. The study revealed that the strategic steps of Fiqh teachers include: (1) building harmonious relationships with students through open communication and empathy; (2) providing a clean, comfortable, and adaptable physical classroom environment; (3) encouraging interaction between students based on Islamic values ​​such as mutual respect and mutual cooperation; (4) motivating student activity through various assignments, group discussions, and question and answer sessions; and (5) implementing discipline through mutually agreed rules and giving awards for student achievements. The main challenges include the variety of student characters and abilities, plus less obedient students, so patience and a flexible teaching approach are needed to maintain a conducive classroom climate. This strategy has proven crucial in creating a safe, orderly, and optimal classroom atmosphere for successful Fiqh learning. The implications of this research for Islamic jurisprudence teachers are the need for teacher training in inclusive classroom strategies, the development of an interaction-based curriculum for Islamic education, and continuous evaluation to overcome obstacles to student character, in order to create productive and adequate learning.